Bacterial Distribution in the Glacier Borehole Meltwater on the Eastern Broknes Peninsula of the Larsemann Hills and Adjacent Lake Water, East Antarctica - Hongpeng Cui; Jibin Han; Bing Li; Youhong Sun; Da Gong; Xiaopeng Fan; Talalay Pavel; Dayi Zhang; Liang Gao; Hongchen Jiang (Microorganisms)
The distribution and assembly mechanisms of microorganisms in Antarctic lakes and glaciers remain poorly understood, despite their ecological significance. This study investigates the bacterial diversity and community composition in glacier borehole meltwater samples from the eastern Broknes Peninsula of the Larsemann Hills and adjacent lake water samples in East Antarctica using high—throughput 16S rRNA gene sequencing. The results show that bacterial diversity in glacier borehole meltwater increased with depth, but remained lower than in lake water. Significant compositional differences were observed between lake and glacier borehole bacterial communities, with higher relative abundances of Actinobacteria, Bacteroidia, Cyanobacteriia, and Verrucomicrobiae in glacier borehole water samples, while Alphaproteobacteria, Gammaproteobacteria, OLB14 (phylum Chloroflexi), Acidimicrobiia, and Thermoleophilia were more abundant in lake samples. These differences were attributed to distinct community assembly mechanisms: stochastic processes (ecological drift and dispersal limitation) dominated in lakes, while both stochastic (ecological drift and homogeneous dispersal) and deterministic (homogeneous selection) processes played key roles in glacier boreholes. This study enhances our understanding of bacterial community assembly and distribution patterns in Antarctic glacier ecosystems, providing insights into microbial biodiversity and biogeochemical cycling in these extreme environments.